Prinsip Jujur Dalam Perdagangan (Tips Manjur Menuju Hidup Makmur) - Mei Santi (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
Concept treacherous life, lie, lie, seems to have become an indispensable longer of any movements of society. A seller, with culasnya deceive the buyer. Though in principle the seller has the obligation to: maintain and care for material to be delivered to the buyer until the time of delivery; submit material that is sold during the predetermined time, at the request of the buyer; bear the material being sold.